COMMUNICATIVE CULTURE AS A CONDITION FOR IMPROVING THE TRAINING OF FUTURE SPECIALISTS (Web of Teachers: Inderscience Research, 2025)
With the formation of human society, there is an urgent need for vocational training, and to solve this problem, first of all, it is necessary to continuously form a communicative culture for each future specialist, and this first requires the study of the basics of human culture, including communicative culture, and, on the one hand, man is part of nature, on the other hand, that he is an example of civilized existence, analyzed and presented reliable information on issues of his socio-cultural essence, the importance of emphasizing his ability to create and master culture.